Therapy and long-term outcomes of acute anal fissure: a high-volume referral centre experience with 623 patients - Fritz, Stefan; Kirsch, Josefine; Schneider, Nikoletta; Kirsch, Jan; Reißfelder, Christoph; Herold, Alexander; Bussen, Dieter G. (Techniques in coloproctology, 2026)
Acute anal fissure is a common cause of severe pain in the anorectal region. The standard treatment is the topical application of a calcium channel blocker or glyceryl trinitrate. Despite acute anal fissure being a common proctologic condition, data on the healing rates and long-term outcomes remain scarce. This study aimed to evaluate data from our centre, with a special focus on long-term follow-up and recurrent disease.
Online veröffentlicht: 6. Januar 2026
Gesehen am 26.02.2026